PERAN USIA DALAM MEMODERASI PENGARUH TECNOLOGY READINESS INDEX TERHADAP NIAT UNTUK MENGGUNAKAN KOMPUTER TABLET DI KOTA DENPASAR - Marto, Kerta Griyadi; Rimbawan, Nyoman Dayuh (E-Jurnal Manajemen, 2013)
This paper was purpose to explore the relationship among the four dimensions of technology readiness index (optimism, innovativeness, discomfort, insecurity) and intention to use computer tablet that moderated by age. The data were analyzed  using multiple linear regression method with no moderating variables (t test) and multiple linear regression method with moderating variables (test of interaction). The result of analysis found that four dimensions of technology readiness index only optimism and innovativeness dimension has a significant influence, while discomfort and insecurity has not influence. The result of multiple regression analysis with moderation variable not found as a moderating variable. Keyword: demographic, age, technology readiness index, optimism, innovativeness, discomfort, insecurity, intention to use.